2003
DOI: 10.1007/3-540-45105-6_83
|View full text |Cite
|
Sign up to set email alerts
|

An Optimization Solution for Packet Scheduling: A Pipeline-Based Genetic Algorithm Accelerator

Abstract: Abstract. The dense wavelength division multiplexing (DWDM) technique has been developed to provide a tremendous number of wavelengths/channels in an optical fiber. In the multi-channel networks, it has been a challenge to effectively schedule a given number of wavelengths and variable-length packets into different wavelengths in order to achieve a maximal network throughput. This optimization process has been considered as difficult as the job scheduling in multiprocessor scenario, which is well known as a NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…When optical technology reaches a mature state and components like optical buffers or all-optical packet header recognition chips will become cost-effective solutions, then optical packet switching (OPS) will become a reality. We should expect then new design and optimization issues for packet switched networks, employing again heuristics and genetic algorithms [109], and following also similar methodologies as in the previously existed communications technology [89,108].…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…When optical technology reaches a mature state and components like optical buffers or all-optical packet header recognition chips will become cost-effective solutions, then optical packet switching (OPS) will become a reality. We should expect then new design and optimization issues for packet switched networks, employing again heuristics and genetic algorithms [109], and following also similar methodologies as in the previously existed communications technology [89,108].…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…But currently there does not exist in the literature any technique specifically designed for searching and finding the best solution among all possible solutions. We will use the converging characteristic of the GA (Sheu et al, 2003) to solve the issue of finding the best solution among all possible solutions generated from all possible combinations of parameters in the FFTSS. By implementing this scheduling technique we will get better transmission efficiency in the FFT execution and consequently it will transmit all users' information in a minimum amount of time.…”
Section: Design Fftss By Using a Genetic Algorithmmentioning
confidence: 99%
“…In recently years, GA has become an important way to solve this problem. It is concluded that crossover and mutation of chromosome and fitness function calculation can converge faster and therefore allow an efficient way to find the approach optimal solution [3].…”
Section: Introductionmentioning
confidence: 99%